La contribución de Sudáfrica al renacimiento africano en el nuevo milenio - Zuma, Jacob (Revista Mexicana de Política Exterior, 2022)
The author lays out a panoramic view of the historical and cultural importance of Africa. He also describes and denounces the causes of the poverty, the precarious economic progress, and the social conflicts that weigh it down. He explains that South Africa and its neighbors are looking for active participation in the new world order. African Unity in order to solve the internal problems of their countries. As a result, the presidents of Algeria, Nigeria and South Africa developed the Millennium Plan for the Development of Africa, that is aimed at finding a solution to the poverty and developmental lag that afflict the continent. African leaders and governing bodies have made progress in negotiations to associate with industrialized countries on the one hand, and on the other, in consolidation of South-South ties to achieve a decent standard of living for all peoples.